Ugodni prostori bez dramaturgije = Pleasant spaces without dramaturgy - Kondža, Nenad (Array, 2010)
Vedran Pedišić, Hrvoje Davidovski, Mladen Hofmann, Gordana Gregurić Miočić, Dragana Knezović: projekt Spa Golfer Hotel, Sveti Martin na Muri, Hrvatska